(NgIDROGEOHIMIQ (B:s ((NfORMIROWANIE HIMI^ESKOGO SOSTAWA PODZEMNYH WOD(B) : (Nu^EBNOE POSOBIE (B/s - (NpITXEWA(B, (NkLARA eFIMOWNAs; (NbRUSLINOWSKIJ(B, (Ns(B. (Na(B.s ((NmOSKWA (B:s (Nmgu(B,s, 1978)
(NbIBLIOGR(B. (93 (NNAZW(B., 37 (NTABL(B.)s
Keywords: (NgEOLOGIQs; (NgIDROGEOHIMIQs